Multi-parameter measurements using optical fibre long period gratings for indoor air quality monitoring - Hromadka, J.; Korposh, Sergiy; Partridge, Matthew; James, Stephen W.; Crump, Derrick; Davis, Frank; Tatam, Ralph P. (Elsevier, 2016)
An array of three long period gratings (LPGs) fabricated in a single optical fibre and multiplexed in the wavelength domain was used to measure simultaneously temperature, relative humidity (RH) and volatile organic compounds (VOCs), which are key indoor air quality (IAQ) indicators. Each LPG sensor was designed with optimised response to a particular measurand. The first, with no surface modification, was used to measure temperature. The second, modified by a mesoporous coating of silica nanoparticles (SiO2 NPs), was used to measure RH and the third, modified with a coating of SiO2 NPs infused with a functional material, p-sulphanatocalix[8]arene (CA[8]), was employed to monitor VOC concentration. The LPGs were fabricated with periods such that they operated at or near the phase matching turning point. The sensors were calibrated in the laboratory and the simultaneous measurement of the key indoor air quality parameters was undertaken in laboratory and office environments. It was demonstrated successfully that the data produced by the LPG sensor array under real conditions was in a good agreement with that produced by commercially available sensors. The average differences between values obtained by the optical fibre sensor and standard temperature and RH sensors were better than 0.5 °C and 5% respectively. Further, the potential application of fibre optic sensors for VOC detection at high concentrations has been demonstrated.
Keywords: Long period grating (LPG); Multiplexing; Phase match turning point (PMTP); Indoor air quality (IAQ); Relative humidity (RH); Volatile organic compounds (VOCs)